ADCC-Mediated CD56dim NK Cell Responses Are Associated with Early HBsAg Clearance in Acute HBV Infection - Wen-Han Yu (Pathogens and Immunity, 2018)
Hepatitis B virus (HBV) affects up to 400 million people worldwide and accounts for approximately one million deaths per year from liver pathologies. Current treatment regimens are effective in suppressing viremia but usually have to be taken indefinitely, warranting research into new therapeutic approaches. Acute HBV infection in adults almost universally results in resolution of viremia, with the exception of immunocompromised persons, suggesting that the immune response can functionally cure or even eradicate HBV infection. Because immunophenotypic and functional studies have implicated a role for Natural Killer (NK) cells in HBV clearance during acute infection, we hypothesized that a distinct NK-cell profile exists in acute HBV infection that could provide information for the mechanism of HBV clearance. Using multivariate flow cytometry, we evaluated the expression of key activating and inhibitory receptors on NK cells, and their ability to respond to classic target cell lines. Multivariate analysis revealed selective perturbation of the CD56 dim NK-cell subset during acute infection, displaying low levels of NKp46+, NKp30+, CD160+ and CD161+ cells. Intriguingly, the CD56 dim NK-cell profile predicted time to HBV surface antigen (HBsAg) clearance from the blood, and distinct NK-cell profiles predicted early (NKp30, CD94, CD161) and late clearance (KIR3DL1, CD158a, perforin, NKp46). Finally, functional analysis demonstrated that early and late clearance tracked with elevated degranulation (CD107a) or IFNγ production, respectively, in response to ADCC-mediated activation. In conclusion, the cytolytic CD56dim NK-cell subset is selectively activated in acute HBV infection and displays distinct phenotypic and functional profiles associated with efficient and early control of HBV, implicating antibody-mediated cytolytic NK-cell responses in the early control and functional cure of HBV infection.